Simultaneous determination of potassium guaiacolsulfonate, guaifenesin, diphenhydramine HCl and carbetapentane citrate in syrups by using HPLC-DAD coupled with partial least squares multivariate calibration - Donmez, Ozlem Aksu; Asci, Burge; Bozdogan, Abdurrezzak; Sungur, Sidika (ELSEVIER, 2011)
A simple and rapid analytical procedure was proposed for the determination of chromatographic peaks by means of partial least squares multivariate calibration (PLS) of high-performance liquid chromatography with diode array detection (H PLC-DAD). The method is exemplified with analysis of quaternary mixtures of potassium guaiacolsulfonate (PG), guaifenesin (GU), diphenhydramine HCl (DP) and carbetapentane citrate (CP) in syrup preparations. In this method, the area does not need to be directly measured and predictions are more accurate. Though the chromatographic and spectral peaks of the analytes were heavily overlapped and interferents coeluted with the compounds studied, good recoveries of analytes could be obtained with HPLC-DAD coupled with PLS calibration. This method was tested by analyzing the synthetic mixture of PG, GU, DP and CP. As a comparison method, a classsical HPLC method was used. The proposed methods were applied to syrups samples containing four drugs and the obtained results were statistically compared with each other. Finally, the main advantage of HPLC-PLS method over the classical HPLC method tried to emphasized as the using of simple mobile phase, shorter analysis time and no use of internal standard and gradient elution. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Partial least squares; HPLC-DAD; Potassium guaiacolsulfonate; Guaifenesin; Diphenhydramine HCl; Carbetapentane citrate; SIMULTANEOUS SPECTROPHOTOMETRIC DETERMINATION; PERFORMANCE LIQUID-CHROMATOGRAPHY; PRINCIPAL-COMPONENT REGRESSION; MULTICOMPONENT ANALYSIS; PSEUDOEPHEDRINE HYDROCHLORIDE; PHARMACEUTICAL-PREPARATIONS; TRIPROLIDINE HYDROCHLORIDE; LIDOCAINE HYDROCHLORIDE; COUGH SYRUP; MIXTURES; Chemistry